Hepatoprotective Activity of Talinum portulacifolium forsk, extract against Paracetamol Induced Hepatic Damage in Rats - junapudi, sunil (Jordan Journal of Pharmaceutical Sciences, 2018)
Talinum portulacifolium Forsk has been traditionally used in Indian medicine as a result of its curative results of hepatitis, gonorrhea and diabetes, it is probably not proof-founded and however folklore has given us many powerful therapies, based on plant sources. So claims which can be made for the protective efficacy of Talinum portulacifolium forsk (family: Portulacaceae) to treat hepatic diseases. The present study focused on investigating the role of alcoholic extract of Talinum portulacifolium forsk. It appreciably prevented the increased in serum Aspartate amino transferase (AST), Alanine amino transferase (ALT), alkaline phosphatase (ALP) and Total serum bilirubin (SB) level in acute liver damage by Paracetamol and elevated the activities of lipid peroxidation (LPO) and glutathione (GSH) in the liver. Histopathological observation of the liver used to be additionally performed to further support the evidence from the biochemical analysis. The observation that these significant protective effect against acute hepatotoxicity induced by Paracetamol of Talinum portulacifolium forsk.